The Development Of Application For Selecting Programmer Experts At The Communication, Information, And Statistics Agency Of Bengkulu Province Using Simple Additive Weighting (Saw) Method - Apriani Purwita Sari; Khairil Khairil; Dimas Aulia Trianggana (Utami Publisher, 2026)
The Communication, Information, and Statistics Agency of Bengkulu Province are a local government agency that plays a role in managing public information and supporting the development of digital services. One of the agency's important needs is the availability of competent expert programmers to support the operation and development of information systems. This study aims to develop a web-based decision support system using the PHP programming language with the CodeIgniter Framework and MySQL database to facilitate the selection process of expert programmers. The Simple Additive Weighting (SAW) method was applied to produce objective assessments based on several criteria, namely age, work experience, certificates, portfolios, interviews, and competency tests, with the greatest weight given to the competency test aspect. A passing grade of 0.75 was set as the threshold for determining which applicants met the qualifications. The results of the study show that the system is capable of automatically calculating scores and rankings according to the predetermined criteria weights. The selection process is faster, more objective, and reduces the potential for errors compared to manual methods. In addition, the system reduces the need for manual recording, thereby increasing administrative efficiency. Thus, this decision support system has been proven to assist agencies in determining prospective programmer experts more accurately and transparently, and has the potential to be applied to the selection process in other government agencies.